PENGARUH NILAI PERUSAHAAN TERHADAP RETURN SAHAM DI PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Wahyuni, Komang Tri (widya balina, 2025)
This study aims to examine the effect of firm value on stock returns. The data used in this research are secondary data obtained from company financial statements, including book value, net income, number of shares, and market price of shares during the period 2020–2024. The sample consists of 20 food and beverage companies listed on the Indonesia Stock Exchange, observed over a five-year period, resulting in a total of 100 observations (20 companies × 5 years). The sampling technique used is purposive sampling. Firm value is measured using the Price to Book Value (PBV) ratio and the Price Earnings Ratio (PER), while stock return is calculated by taking the price at time t minus the price at time t–1, then divided by the price at time t–1. The data were analyzed using multiple linear regression. The results of the study indicate that PBV has a positive and significant effect on stock returns, whereas PER does not have a significant impact. These findings suggest that firm value, as reflected by PBV, has a more consistent influence on stock returns compared to PER. This may be due to the fluctuating nature of profits, stock prices, and the number of shares outstanding, which vary across large and small companies in the food and beverage sector. Therefore, this study recommends incorporating additional variables, such as firm size and the liquidity of outstanding shares (free float), to minimize potential bias in the analysis.